2021
DOI: 10.18662/lumproc/gekos2021/16
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the “Zoom Fatigue” Phenomenon and Ways of Managing It

Abstract: The context of the COVID 19 pandemic has forced managers and entrepreneurs to review how they run their businesses and guide their employees. The new normality has brought with it a number of challenges and changes that have produced immediate and profound effects both in the way business is conducted, the online negotiations giving a formal and less human character, and in the way the employees perceive the work carried out exclusively online. Research has revealed a new phenomenon called "Zoom Fatigue" which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In classes using conventional online videoconferencing, difficulties in student-student or student-lecturer interactions and limitations in communication methods have been noted. 3,18 Furthermore, long-term repetitive use of videoconferencing programs can cause "Zoom fatigue" for instructors and learners. 19 Meanwhile, it is possible to move in the space within a metaverse classroom and students can easily perceive the learning space and experience learning that combines group activities and spatiality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In classes using conventional online videoconferencing, difficulties in student-student or student-lecturer interactions and limitations in communication methods have been noted. 3,18 Furthermore, long-term repetitive use of videoconferencing programs can cause "Zoom fatigue" for instructors and learners. 19 Meanwhile, it is possible to move in the space within a metaverse classroom and students can easily perceive the learning space and experience learning that combines group activities and spatiality.…”
Section: Discussionmentioning
confidence: 99%
“…The metaverse platform was identified as a learning tool that could improve learners' concentration because it was easy to use and facilitated participation through controlling an avatar. In classes using conventional online videoconferencing, difficulties in student-student or student-lecturer interactions and limitations in communication methods have been noted 3,18. Furthermore, long-term repetitive use of videoconferencing programs can cause “Zoom fatigue” for instructors and learners 19.…”
Section: Discussionmentioning
confidence: 99%
“…Social presence is a digital psychological factor that should be continuously noted even after digital transformation is expected to accelerate. Meanwhile, several studies found that the technical quality of video conferencing can reduce video conference fatigue, which has been newly introduced after the March 2020 pandemic [17][18][19][20]. Additionally, Cho and Lim [15] and Kwon, Kim, and Chang [21] found that the interaction quality of real-time internet broadcasting has a positive effect on viewers' flow.…”
Section: Video Conference Qualitymentioning
confidence: 99%